The Role of Foundation Grantmakers in Responding to Community Aging: Maine Health Access Foundation - Wolf, Wendy (Maine Policy Review, 2015)
Wendy J. Wolf of the Maine Health Access Foundation responds to a series of questions about the role of grantmakers in responding to community aging.
Keywords: aging; Maine; grantmakers; philanthropy